Risk-Informed Settlement Development: A Landslide Mitigation Framework for Transmigration Areas in Polewali Mandar - Widiyanto, Bayu; Parung, Herman; Tumpu, Miswar; Widodo, Sri; Hatta, Mukhsan Putra (Engineering, Technology & Applied Science Research, 2025)
Landslides pose a major threat to settlements in transmigration zones, highlighting the need for a risk-based approach in sustainable land planning. This study introduces a Risk-Informed Settlement Development Framework to evaluate the landslide vulnerability in Ratte Village, Polewali Mandar Regency, which covers 625,000 km². A spatial analysis method was employed, combining various thematic layers, including geology, topography, land use, and rainfall intensity, to assess the risk levels using scoring and weighting techniques. The results show that much of the settlement area falls within moderate to high-risk zones, mainly due to steep slopes, heavy rainfall, and unsuitable land use practices. However, some low-susceptibility areas offer safer options for future settlement expansion. The novelty of this study lies in integrating landslide risk reduction with a proactive feasibility assessment for settlement development, shifting from traditional hazard mapping to forward-looking, adaptive land use planning. This research offers a decision-support tool that not only identifies risks, but also helps guide the strategic settlement relocation and development through multi-criteria spatial analysis. Future research should focus on enhancing the framework by including real-time monitoring data, socio-economic vulnerability indices, and climate change projections to improve the predictive accuracy and applicability across different geographic regions. The proposed framework serves as an essential tool for policymakers and planners to ensure the long-term safety and resilience of transmigrant communities in landslide-prone areas.